Overview of presurgical assessment and surgical treatment of epilepsy from the Italian League Against Epilepsy. (4th October 2013) - Guerrini, Renzo; Scerrati, Massimo; Rubboli, Guido; Esposito, Vincenzo; Colicchio, Gabriella; Cossu, Massimo; Marras, Carlo Efisio; Tassi, Laura; Tinuper, Paolo; Paola Canevini, Maria; Quarato, Pierpaolo; Giordano, Flavio; et al.
Summary: The Commission for Epilepsy Surgery of the Italian League Against Epilepsy (LICE) presents an overview of the techniques and methodologies of presurgical evaluation and of the surgical treatment of epilepsies. This overview is the result of the experience developed in the past years in the major Italian centers where programs of epilepsy surgery have been established, and it has the aim of offering a quick and easy reference tool for those involved in the treatment of patients with epilepsy. The sharing of different experiences has the additional aim of conforming and disseminating the employed techniques as well as the methods of selection and evaluation of patients. The synthetic coverage of the main issues concerning the presurgical workup and the available surgical options will hopefully provide a framework that may integrate and develop the contributions of every single center, in one of the more complex, challenging, and dynamic areas of neurological sciences.